2017
DOI: 10.2196/jmir.7180
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Two Web-Based Interventions for Chronic Cancer-Related Fatigue Compared to an Active Control Condition: Results of the “Fitter na kanker” Randomized Controlled Trial

Abstract: BackgroundApproximately one third of all patients who have been successfully treated for cancer suffer from chronic cancer-related fatigue (CCRF). Effective and easily accessible interventions are needed for these patients.ObjectiveThe current paper reports on the results of a 3-armed randomized controlled trial investigating the clinical effectiveness of two different guided Web-based interventions for reducing CCRF compared to an active control condition.MethodsSeverely fatigued cancer survivors were recruit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
138
1
8

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(149 citation statements)
references
References 45 publications
2
138
1
8
Order By: Relevance
“…A small waitlist randomized-controlled trial (RCT) about an online group mindfulness-based intervention (MBI) for cancer patients revealed positive effects on stress symptoms and mood disturbances [14]. Moreover, an active-controlled study showed eMBCT could reduce cancer-related fatigue [15]. Our research group conducted a large RCT (the BeMind project) comparing group MBCT with individual eMBCT, showing that both types of treatments are superior to usual care [16].…”
Section: Introductionmentioning
confidence: 93%
“…A small waitlist randomized-controlled trial (RCT) about an online group mindfulness-based intervention (MBI) for cancer patients revealed positive effects on stress symptoms and mood disturbances [14]. Moreover, an active-controlled study showed eMBCT could reduce cancer-related fatigue [15]. Our research group conducted a large RCT (the BeMind project) comparing group MBCT with individual eMBCT, showing that both types of treatments are superior to usual care [16].…”
Section: Introductionmentioning
confidence: 93%
“…Clients mainly suffer from severe cancer-related fatigue, anxiety, trauma, stressrelated and depressive disorders, relationship problems and/or prolonged grief disorder. Since 2009 the institute offers specific internetbased interventions for cancer patients, such as Mindfulness-Based Cognitive Therapy (MBCT) for cancer-related fatigue 1,2 and Anxiety and Depression, 3,4 self-help and blended Cognitive Behavioural Therapy (CBT) for fear of cancer recurrence 5,6 within a secure environment.…”
Section: Video-consultsmentioning
confidence: 99%
“…peak oxygen uptake, heart rate, rating of perceived exertion (RPE) and blood lactate) is reported for the purpose of characterizing the test and describing the sub-study participants. Borg's RPE scale (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) [29] was administered according to published instructions [30]. is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) preprint…”
Section: Laboratory Visitmentioning
confidence: 99%
“…CRF that continues for months or years has been called chronic CRF [4] or post-cancer fatigue [6]. Although there is no strict consensus on when CRF can be described as chronic, we and other research groups [6,7] define chronic CRF/post-cancer fatigue as clinically-relevant CRF that continues for ≥3 months after the completion of cancer treatment.…”
Section: Introductionmentioning
confidence: 99%